Respuesta :

Answer:

27

Step-by-step explanation:

If p = 2q2 – 5 and q = 10 - 3r, find a. p when r equals 2 7. b. r when p equals 67. This problem has been solved!

Answer:

r = [tex]\frac{4}{3}[/tex]

Step-by-step explanation:

When p = 67 , then

2q² - 5 = 67 ( add 5 to both sides )

2q² = 72 ( divide both sides by 2 )

q² = 36 ( take square root of both sides )

q = [tex]\sqrt{36}[/tex] = 6

Then

6 = 10 - 3r  ( subtract 10 from both sides )

- 4 = - 3r ( divide both sides by - 3 )

[tex]\frac{-4}{-3}[/tex] = r , that is

r = [tex]\frac{4}{3}[/tex]